Interactive effects of polymethyl methacrylate (PMMA) microplastics and salinity variation on a marine diatom Phaeodactylum tricornutum. (February 2022) - Dong, Jingwei; Li, Linqing; Liu, Qiaoqiao; Yang, Mengting; Gao, Zheng; Qian, Pingkang; Gao, Kun; Deng, Xiangyuan
Abstract: Until now, knowledge about the interactive effects of microplastics and environmental factors on primary producers is quite limited. In this work, a marine diatom ( Phaeodactylum tricornutum ) was exposed to polymethyl methacrylate (PMMA) microplastics at different salinities (25, 35, and 45‰) for 10 days in order to study their interactive effects. Results showed that growth of P. tricornutum was negatively affected by PMMA microplastics and salinity variation with a minimum EC50 value of 91.75 mg L −1 . Photosynthetic activity of P. tricornutum was also inhibited by the two factors, and their interactive effects on chlorophyll fluorescence parameters ( F v / F m and Φ PSII ) were significant. In the algal cells, soluble protein accumulated, activities of two antioxidant enzymes changed, and malondialdehyde (MDA) content increased when this diatom was exposed to the microplastics at different salinities. These data would help to evaluate the risks of microplastics to primary producers under different environmental factors. Graphical abstract: Image 1 Highlights: We first studied interactive effects of PMMA microplastics and salinity variation. The interactive effects were significant on the growth of P. tricornutum. Photosynthetic activity of this diatom was obviously affected by the two factors. The two factors caused physiological and biochemical changes in the algal cells.